The Role of Islamic SuKuks (Bonds) in Supporting Shareholding Companies : Damac Case Study (2014-2018) - Farid , MECHERI; Miloud , BORNI (Milev Journal of Research and Studies, 2020)
Islamic Sukuk (bonds) are one of the most important and innovative financial instruments, that have occupied an important position on the stock markets with its various types and forms. As it contributed to covering the financing needs that are necessary to support the joint stock companies listed on the financial markets. The purpose of this study is to reveal the characteristics of Islamic Sukuk, in addition to the mechanisms of issuance, trading and using it as a financing source. The study also aims to identify and highlight the role of Sukuk in financing the joint stock companies as a case of study listed on Dubai financial market. The study concluded that Islamic Sukuk play a growing role in financing the joint stock companie as a case of study listed on Dubai financial market during the period 2014-2018. There was an increasing use of Sukuk as a funding source during 2014-2018 by DAMAC.